AN ANALYSIS OF MOTHER TONGUE INTERFERENCE IN ENGLISH PRONUNCIATION - Ilva Widiantari; Aunurrahman Aunurrahman; Sahrawi Sahrawi (IKIP PGRI Pontianak, 2021)
This research aimed to investigate the interference of the Malay language in Pronouncing English voiceless stops by EFL students in Pontianak. The design of this research was a descriptive study. The total participants were 15 EFL students whose mother tongue is Malay. This research used a pronunciation test to collect pronunciation data through an audio recorder as the main tool. Pronunciation test sheet consisted 21 English words contains English voiceless stops phoneme /p/, /t/, and /k/. Based on the research findings, after conducting a pronunciation test the data showed that from 315 English words that had been tested there were 129 words in total found mispronounced by the students. Mostly, mispronunciation happened when pronouncing phoneme /p/ that was 56 times from 105 chances, followed by phoneme /t/ that was 42 times from 105 chances and phoneme /k/ which 31 errors from 105 chances. Based on the research findings, mother tongue indicated interfere students` pronunciation in pronouncing English words at Pontianak. Keywords: Mother tongue, Interference, English pronunciation.